Offering strategy of price-maker energy hubs in integrated local electricity and heat markets - Norouzi, Saba; Dadashi, Mojtaba; Haghifam, Sara; Laaksonen, Hannu; Zare, Kazem (Elsevier, 2025)
Integrated energy systems are considered a promising solution for increasing the flexibility of energy systems and accommodating more renewable energy resources to achieve decarbonization targets. In the context of EU countries, power-to-heat technologies are useful for achieving sector-coupling aspirations. However, designing an appropriate market-based platform that facilitates efficient cooperation and interaction among various power and heat units is crucial. Integrated energy systems in the form of energy hubs play an important role in this market-based framework as interface agents among different energy carriers. To this end, the paper proposes a market design based on a simultaneous market clearing in local power and heat markets, in which a price-maker energy hub participates in an attempt to maximize its revenue by offering in the joint markets. Hence, a bi-level programming method is used, in which, at the upper level of the problem, the focus is on maximizing the entity’s profit, while the lower level addresses the local integrated market-clearing process. Second-order stochastic dominance constraints are also imposed on the problem to mitigate the studied energy hub’s market participation risks. The problem is solved in two different sections, including the risk-neutral and risk-averse perspectives of the energy hub operator. The results of the proposed risk-averse bi-level scheme are demonstrated to be appropriate for each EH to promote its benefit in the joint power and heat markets while controlling the profit distribution and the risk of market participation based on the operator’s market preference. The results indicate that implementing the proposed approach allows EH’s owner to adjust its day-ahead offers in real time using flexible units in both power and heat forms. Also, imposing second-order stochastic dominance constraints enables the EH’s operator to adjust its profit in the worst scenario based on its preference in a wide range, 873 € to 1737 €, which is not possible in other risk-management methods like CVaR.
Keywords: Energy hubs; Integrated energy systems; Local integrated electricity and heat markets; Bi-level programming approach; Second-order stochastic dominance risk-management method; fi=Sähkötekniikka|en=Electrical Engineering|